Teknologi Tanaman Padi Sistem Tanam Benih Langsung dengan Hambur di Dataran Tinggi Sumatera Utara (Studi Kasus di Kabupaten Humbang Hasundutan) - Imelda S. Marpaung; Tumpal Sipahutar; Deddy R. Siagian; Tommy P. (Proceedings Series on Physical & Formal Sciences, 2021)
Rice farmers in Humbang Hasundutan Regency still maintain rice technology with the scattering system because farmers feel this planting system to be still relevant to the condition of available resources in Humbang Hasundutan Regency. The study of direct seed planting system technology in Humbang Hasundutan Regency was carried out using a survey method by conducting interviews with key informants in Polung Subdistrict, Humbang Hasundutan Regency. From the interview results, it was found that the transplanting system technology, both with tiles and jajar legowo in Humbang Hasundutan Regency, did not give significantly different results compared to the scattering system. The results of the farming analysis obtained show that the scattering system gives an R/C value of 1.88 compared to the transplanting system of 1.94 R/C.